2022
DOI: 10.3390/cells11040649
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Mesenchymal Transition (EMT) and Associated Invasive Adhesions in Solid and Haematological Tumours

Abstract: In solid tumours, cancer cells that undergo epithelial mesenchymal transition (EMT) express characteristic gene expression signatures that promote invasive migration as well as the development of stemness, immunosuppression and drug/radiotherapy resistance, contributing to the formation of currently untreatable metastatic tumours. The cancer traits associated with EMT can be controlled by the signalling nodes at characteristic adhesion sites (focal contacts, invadopodia and microtentacles) where the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 144 publications
(235 reference statements)
0
27
0
Order By: Relevance
“…EMT is a complex process involving multiple signaling pathways and transcription factor regulation, the up-regulation of mesenchymal genes and suppression of epithelial genes lead to the transformation of cell morphology and acquisition of stronger invasive migration capability ( 66 ). Many changes in cellular shape and vitality, such as loss of cellular polarity, the disappearance of intercellular adhesion, and the acquisition of enhanced motility, which promote cells to fall off from tumor tissues and invade into blood vessels ( 64 , 67 , 68 ). EMT process facilitates the secretion of matrix metalloproteinase (MMP), which degrades the extracellular matrix to cause cell migration, tissue invasion and blood vessel infiltration ( 69 ).…”
Section: Emt and Ctcsmentioning
confidence: 99%
See 2 more Smart Citations
“…EMT is a complex process involving multiple signaling pathways and transcription factor regulation, the up-regulation of mesenchymal genes and suppression of epithelial genes lead to the transformation of cell morphology and acquisition of stronger invasive migration capability ( 66 ). Many changes in cellular shape and vitality, such as loss of cellular polarity, the disappearance of intercellular adhesion, and the acquisition of enhanced motility, which promote cells to fall off from tumor tissues and invade into blood vessels ( 64 , 67 , 68 ). EMT process facilitates the secretion of matrix metalloproteinase (MMP), which degrades the extracellular matrix to cause cell migration, tissue invasion and blood vessel infiltration ( 69 ).…”
Section: Emt and Ctcsmentioning
confidence: 99%
“…EMT is believed to play an important role in tumor occurrence and progression. The studies have demonstrated that the expression of EMT markers is associated with an aggressive malignant phenotype and with poor prognosis in cancer patients ( 65 , 67 , 70 ).…”
Section: Emt and Ctcsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, EndoMT recurs postnatally during the development of various cardiovascular diseases (CVDs), such as atherosclerosis, adult valve diseases, myocardial fibrosis, and pulmonary arterial hypertension (PAH) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In the EndoMT transitional process, endothelial cells progressively lose endothelial-specific markers and gain mesenchymal phenotypes [ 45 ]. The expression of cell–cell adhesion proteins is downregulated, but mesenchyme-specific factors are increased [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is a dynamic cellular reprogramming process through which epithelial cells undergo morphological changes characterized by loss of cell-cell adhesion and acquisition of mobile fibroblast-like phenotype. A previous study demonstrated that EMT progression participated in embryonic development and tissue remolding ( Greaves and Calle, 2022 ). Subsequent evidence suggested that the aberrant activation of the EMT process promoted metastasis, invasion, and drug resistance of multiple epithelial carcinomas, such as gastric carcinoma, breast cancer, and lung cancer ( Menju and Date, 2021 ; Azimi et al, 2022 ; Buyuk et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%